Strategi Pendistribusian Zakat Produktif Perdagangan pada BAZNAS Kota Padang Panjang - Nopiardo, Widi; Nurhidayat, Wahyu (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Padangsidimpuan, 2021)
Abstract The problems raised in this article from year to year, namely from 2016-2018 the number of productive zakat mustahik at BAZNAS in Padang has always increased, but in 2019 it has decreased. The distribution of productive zakat funds from 2016-2019 was more dominant for the trading business. The complexity of the problem in the distribution of productive zakat certainly requires the right strategy in distribution, so it is necessary to know what strategy is carried out by BAZNAS Padang Panjang city. The type of research that the author does is field research (field research) with a qualitative descriptive approach. The primary data sources in this study were the Head of BAZNAS Padang Panjang City, Padang Panjang City BAZNAS Secretariat Staff, and Mustahik. The secondary data sources in this research are the accountability reports of BAZNAS Padang Panjang City 2016-2019, brochures, monthly reports, and documents related to BAZNAS Padang Panjang City. Data collection techniques in this study were interview and documentation techniques. The results showed that the trade-productive zakat distribution strategy was carried out by collecting data on mustahik candidates, verifying mustahik proposals, conducting surveys of mustahik, discussing and determining survey results, distributing zakat, and monitoring mustahik businesses.Keywords: Strategy, Distribution, Productive Zakat